Policy suggestions for tapping the potential of ocean carbon sinks in the context of “double carbon” goals in China - Wei, Xuezhi; Wang, Quansheng (Frontiers in Marine Science, 2024)
China is rich in marine resources and has excellent potential for the development of oceanic carbon sinks. Ocean carbon sinks have shown broad application prospects, but the technical system for trading has not yet been perfected, the relevant legislation has not yet been established, etc. China should actively promote scientific research on ocean carbon sinks, improve the technical system of ocean carbon sinks, establish an ocean carbon sink trading system, and develop the eco-economy of ocean carbon sinks. It should also establish a sound system of laws and regulations to explore the potential of oceanic carbon sinks and contribute to the realization of China’s dual-carbon goal.